2023
DOI: 10.12688/f1000research.129036.2
|View full text |Cite
|
Sign up to set email alerts
|

Studying ancient human oral microbiomes could yield insights into the evolutionary history of noncommunicable diseases

Abstract: Noncommunicable diseases (NCDs) have played a critical role in shaping human evolution and societies. Despite the exceptional impact of NCDs economically and socially, little is known about the prevalence or impact of these diseases in the past as most do not leave distinguishing features on the human skeleton and are not directly associated with unique pathogens. The inability to identify NCDs in antiquity precludes researchers from investigating how changes in diet, lifestyle, and environments modulate NCD r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 130 publications
0
4
0
Order By: Relevance
“…Calculus samples before and after the introduction of tobacco showed highly similar species profiles [34]. The most abundant bacterial taxa detected in many historical calculus samples included several commensal bacterial species commonly found in the human oral cavity, such as Streptococcus sanguinis, Streptococcus cristatus, and Lautropia mirabilis [7,37].…”
Section: Modern and Ancient Oral Microbiomementioning
confidence: 95%
See 1 more Smart Citation
“…Calculus samples before and after the introduction of tobacco showed highly similar species profiles [34]. The most abundant bacterial taxa detected in many historical calculus samples included several commensal bacterial species commonly found in the human oral cavity, such as Streptococcus sanguinis, Streptococcus cristatus, and Lautropia mirabilis [7,37].…”
Section: Modern and Ancient Oral Microbiomementioning
confidence: 95%
“…In healthy adults, the majority of species belong to the bacterial phyla Firmicutes, Proteobacteria, Actinobacteria, Bacteroidetes and Fusobacteria [33]. Since environmental and lifestyle factors influence oral health and disease, ancient dental calculus provides an opportunity to understand the relationship between microbial patterns and oral health and disease in key transition periods in our history [34]. In order to answer the research question "what scientific findings on oral health and diseases can be found from human oral microbiome data collected on ancient dental calculus samples?…”
Section: Introductionmentioning
confidence: 99%
“…In addition to periodontal pathogens, the altered composition of the oral microbiota has also been reported in participants with AD in several studies. For instance, a higher abundance of Moraxella, Leptotrichia, Sphaerochaeta, Lactobacillales, Streptococcaceae, Firmicutes/Bacteroidetes, and a significant reduction of Rothia and Fusobacterium was observed in the oral microbiota of AD participants [165][166][167]. Interestingly, similar to P. gingivalis, other Gram-negative bacteria-Moraxella, Leptotrichia, and Sphaerochaetafound in the oral cavity were linked to Aβ plaque formation through the production of LPS in the brains of AD patients [166,168].…”
Section: A Potential Role Of the Oral Microbiota In Ad?mentioning
confidence: 98%
“…For example, accurate age estimation techniques may provide key information into how the oral microbiome changes during lifespans in archeological populations (Gancz & Weyrich, 2023). However, such analyses become infeasible if information regarding the age estimation techniques is not specified (Bailey & Vidoli, 2023;Clark et al, 2020;Milner & Boldsen, 2012).…”
Section: Skeletal Sex Estimationsmentioning
confidence: 99%
“…In addition to these microscopic and biomolecular investigations, dental calculus has been utilized by bioarchaeological researchers as a marker of frailty and disease (DeWitte & Bekvalac, 2010;Yaussy & DeWitte, 2019). Recently, researchers have even attempted to combine these macroscale analyses with metagenomic approaches to provide more detailed insights into the health of ancient populations (Gancz et al, 2023;Gancz & Weyrich, 2023).…”
Section: Introductionmentioning
confidence: 99%